An investigation of the effects of fulvic and humic acids on the absorption of selected drugs, vitamins and minerals using the everted mouse gut model - Cromarty, Allan Duncan (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2015.